ABUNDANCE AND DIVERSITY OF SOIL INSECTS ON LOCAL TIDORE CHILI PEPPERS - Betty Kadir Lahati; Helda Sabban; Suleyman Suleyman (Journal of Innovation Research and Knowledge, 2026)
Soil insects play essential ecological roles in agricultural ecosystems through decomposition, nutrient cycling, biological regulation, and maintenance of soil environmental quality. However, information regarding soil insect diversity associated with local chili cultivation in Tidore remains limited. This study aimed to analyze the diversity, abundance, and community structure of soil insects in local chili (Capsicum annuum L.) cultivation areas in Tidore and evaluate their ecological significance as indicators of agroecosystem conditions. The research was conducted using a survey method with direct field observation and pitfall trap sampling. Collected specimens were preserved and identified to family level, and ecological analysis was performed using species richness, Shannon–Wiener diversity index (H′), evenness index (E), and dominance index (C). A total of 186 individuals belonging to eight families and six insect orders were recorded. Hymenoptera (Formicidae) showed the highest abundance among collected taxa. The ecological analysis indicated moderate diversity (H′ = 1.84), high evenness (E = 0.88), and low dominance (C = 0.22), suggesting relatively balanced community structure and favorable environmental conditions for soil insect development. The findings demonstrate that local chili cultivation areas in Tidore maintain ecological characteristics capable of supporting diverse soil insect communities and sustaining agroecosystem functions. This study provides baseline ecological information that may support biodiversity conservation and sustainable agricultural management in local horticultural systems